Je Bahalap Ihapan Je Maram Inganan: Harnessing of Positive Values from the Kwangkay Tradition for Preventive Strategies Confronting Risks of Society 5.0 - Aghnia Khilya Rahmaniati; Ananda Nayla Kamil; Haidar Zeeka Fachrezi; Kayla Najmina Syamila; Mujadid Idul Haq; Nasywa Mutia Gatari1 (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan